Variations in methylmercury contamination levels and associated health risks in different fish species across three coastal bays in China - Liu, Tao; An, Mingming; Chen, Jingrui; Liu, Yuanyuan; Chao, Le; Liu, Jichen; Zhang, Mingliang (Frontiers in Environmental Science, 2024)
The growing atmospheric mercury (Hg) emissions in China have raised ongoing concerns regarding contamination in marine fish. To better understand the pollution patterns and associated risks, we examined methylmercury (MeHg) content in demersal and pelagic fish from four commonly found families in three geographically distinct bays along the Chinese coast. We identified significant spatial variations in MeHg levels within the same fish family across regions.Specifically, fish collected from the Beibu Gulf in the South China Sea consistently exhibited significantly higher MeHg levels compared to those from the Laizhou Bay in the Northeast and/or Haizhou Bay in the East of China. In contrast, MeHg levels in fish collected from Haizhou Bay consistently remained the lowest. Within each region, we observed significantly higher MeHg concentrations in demersal species compared to pelagic species. This trend was particularly evident in fish species including bartail flathead (Platycephalus indicus), small-scale tongue sole (Cynoglossus microlepis) and greater lizardfish (Saurida tumbil) from the Beibu Gulf (0.50, 0.21 and 0.18 mg/kg dw, respectively), as well as bartail flathead and slender lizardfish (Saurida elongata) from Laizhou Bay (0.09 and 0.12 mg/kg dw, respectively). By comparison, MeHg content in silver pomfret (Pampus argenteus) from all three regions consistently remained relatively lower than in other species. Using target hazardous quotient (THQ) calculations, we estimated potential health risks in local populations associated with the consumption of the studied fish species. Our results showed a lack of apparent health risks to local residents, as all THQ values obtained from the three regions fell within the safe limits (0.02-0.94). However, it remains important to conduct additional assessments and spatiotemporal monitoring that encompass a broader range of species and regions.